Pentingnya akhlak peneliti biologi sebagai karakteristik peneliti yang baik dan kredibel di zaman modern - Fakhruddin, Muhammad Zaidaan 'Abid (Maliki Interdisciplinary Journal, 2026)
Morals are the character or temperament a person must have in order to create a harmonious and peaceful life. Morals must also be possessed by a researcher as a characteristic of a good and credible researcher in modern times where morals have begun to fade. Morals are not only related to human relationships with God, but also strengthen human relationships with other humans and nature. In Islam, noble morals are a reflection of a person's quality of life and serve as a guide for humans, especially in the world of science where morals must be possessed by a researcher. Science comes from Allah s.w.t. Humans only discover. Muslim scientists such as Ibn Sina, Abu Musa Al-Khwarizmi, Ibn Rusd, Abu Al Haitham, Al-Biruni and others were researchers with morals so that the results of their research were used as references in various fields and became insights into science. Morals are very influential for a researcher because they can influence research results which must be valid, accurate and of good quality. Therefore, a researcher must have several morals, including honesty, which is very important for the validity and accuracy of research results, trustworthiness, which influences the quality of research results, and responsibility, which determines the sincerity of a researcher.